Active Boulder Falls in Terra Sirenum, Mars: Constraints on Timing and Causes. Issue 20 (14th October 2021) - Grindrod, Peter M.; Davis, Joel M.; Conway, Susan J.; de Haas, Tjalling
Abstract: We use time series images to identify significant active boulder falls in an impact crater on Mars. Evidence for active boulder falls include boulder trails with impact marks from bouncing and rolling, and dark patches from boulder impacts away from the base of the crater walls. We were able to define three time periods with active boulder falls and additional slope streak formation, for which we refined the most significant activity to a time period between January 2012 and March 2013. A search of 236 images within 500 km of the study site identified two further sites with similar, but reduced, activity during the same time period. We discuss plausible mechanisms for the boulder fall activity, and conclude that the local geology and crater age is likely to be of significant importance. Our method of identifying and highlighting such activity will allow further studies of active surface processes on Mars. Plain Language Summary: Mars has active surface processes, driven by environmental effects and meteorite impacts. But can interior processes cause changes at the surface today? Answering this question will help expand the recent discoveries of marsquakes by NASA's InSight lander, by identifying possible regions of seismic activity on the planet. Here we use time series orbital images to identify significant boulder falls in a crater on Mars. The temporal resolution of different cameras allows us to refine the timing of the most significant change to a time period of within just over an Earth year. Searching all similar images within 500 km revealed two further sites with similar, but reduced, activity within the same time period. Although our results do not rule out exogenic processes, the concurrent activity in several sites at similar times offers evidence of possibly related causes of boulder fall activity. Key Points: Active boulder falls identified in a near‐equatorial impact crater on Mars Timing of most significant activity refined to a period of just over one Earth year Local geology and crater age likely important, but not only, causes of boulder activity